The Effect of the Neuman Systems Model-Based Training and Follow-up on Self-Efficacy and Symptom Control in Patients Undergoing Chemotherapy - Dural, Gul; Saritas, Seyhan Citlik (Sage Publications Inc, 2024)
In this article, the authors aimed to determine the effect of the training and follow-up based on the Neuman systems model provided to patients undergoing chemotherapy on their self-efficacy and symptom control. The study was carried out with a randomized controlled experimental study model design. The sample consisted of 102 patients including 52 in the experimental group and 50 in the control group. The data were collected using the Patient Information Form, the Cancer Behavior Inventory-Brief (CBI-B), and the Edmonton Symptom Assessment Scale (ESAS). A personal training program prepared according to the Neuman systems model was applied to the experimental group patients. In the intergroup comparison of the experimental and control group patients, there was an increase in the posttest CBI-B scores and a decrease in the ESAS scores in the experimental group compared to the control group, and the intergroup difference was statistically significant (p < .05). According to the results, to improve the self-efficacy and symptom control in patients undergoing chemotherapy, using this education and follow-up program is recommended.
Keywords: chemotherapy; Neuman systems model; self-efficacy; symptom control